The geopolitical effects of unemployment on Iraq (Journal of the College of Basic Education, 2022)
Unemployment is one of the complex phenomena that Iraq suffers from, especially youth unemployment, which results in serious repercussions on the individual in particular and on Iraqi society in general. Therefore, the research aims to study unemployment, its concept and types, and then investigate its causes and methods of treatment, because unemployment has geological effects in terms of the political situation And the economy of the country, which requires searching for the best and fastest measures to solve the problem that the country is exposed to through developing proposed treatments to reduce the phenomenon of unemployment by adopting a comprehensive strategy to build the economy and politics, diagnose youth problems, and build a comprehensive and evolving information base.